2021
DOI: 10.1021/acsanm.0c03409
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Coated with MnO2 Nanoparticles as Thin Film Composite Membranes for Organic Solvent Nanofiltration

Abstract: A thin film composite (TFC) membrane with superior characteristics for organic solvent nanofiltration (OSN) was successfully prepared. Accordingly, a state-of-the-art polyethylene (PE) membrane support was first prepared through etching the polystyrene (PS)/styrene–ethylene–butylene–styrene (SEBS) phase, as the dispersed phase, from the fabricated PE/SEBS/PS composite using the solvent extraction technique. Different compositions were fabricated so that a suitable ultrafiltration membrane support could be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 70 publications
(160 reference statements)
0
28
0
Order By: Relevance
“…45 Furthermore, it is noteworthy that in this method, the pore size is defined as the dispersed phase size, which has been extracted from the sheet, and so the dispersed phase is regarded as the porogen phase. 16,45 The mechanical properties of the PE membrane, including the tensile strength, elongation at break, and Young's modulus, were evaluated and compared with the commercialized SRNF supports, as listed in Table S2. Based on this table, it can be confirmed that the PE membrane possesses greater mechanical properties than the commercialized ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Furthermore, it is noteworthy that in this method, the pore size is defined as the dispersed phase size, which has been extracted from the sheet, and so the dispersed phase is regarded as the porogen phase. 16,45 The mechanical properties of the PE membrane, including the tensile strength, elongation at break, and Young's modulus, were evaluated and compared with the commercialized SRNF supports, as listed in Table S2. Based on this table, it can be confirmed that the PE membrane possesses greater mechanical properties than the commercialized ones.…”
Section: Resultsmentioning
confidence: 99%
“…13−15 The porous support membrane is generally prepared by a variety of cross-linked polymers, for example, polyimides. 8,16 However, it is vital to cross-link these membranes so that they can withstand in chemically harsh media. 17 According to the literature, huge amounts of solvents, post-treatments, and time are necessary in order to carry out the cross-linking step.…”
Section: Introductionmentioning
confidence: 99%
“…CMP membrane, which is superior to most reported organic solvent nanofiltration membranes. [187,188]…”
Section: Nanofiltrationmentioning
confidence: 99%
“…A stable methanol permeance of 28 L m −2 h −1 bar −1 was achieved for the CMP membrane, which is superior to most reported organic solvent nanofiltration membranes. [ 187,188 ]…”
Section: Functional Exploration and Applicationsmentioning
confidence: 99%
“…Nanoparticles, such as ZrO 2 , Al 2 O 2 , SiO 2 , Fe 3 O 4 , ZnO, and TiO 2 , have been reported to impart hydrophilicity onto modified PA-TFC membrane surfaces [8][9][10][11]. As such, their incorporation into PA-TFC membranes improves the water permeability and fouling resistance of PA-TFC membrane surfaces.…”
Section: Introductionmentioning
confidence: 99%